MP18: Addressing unrealistic expectations: a novel transition to discipline curriculum in emergency medicine. (May 2019) - Costello, L.; Argintaru, N.; Wong, A.; Simard, R.; Chacko, M.; Meshkat, N.
Abstract : Innovation Concept : Emergency medicine (EM) programs have restructured their training using a Competence by Design model. This model emphasizes entrustable professional activities (EPAs) that residents must fulfill before advancing in their training. The first EPA (EPA 1) for the transition to discipline (TTD) stage involves managing the unstable patient. Data from the University of Toronto (U of T) program suggests residents lack enough exposure to these patient presentations during TTD – creating a disconnect between anticipated clinical exposure and the expectation for residents to achieve competence in EPA 1.Methods : To overcome this gap, U of T EM faculty specifically targeted EPA 1 while designing the TTD curriculum. Kern's six-step approach to curriculum development in medical education was used. This six-step approach involves: problem identification, needs assessment, goals and objectives, education strategies, implementation and evaluation. To maximize feasibility of the new curriculum, existing sessions were mapped against EPAs and required training activities to identify synchrony where possible. Residents were scheduled on EM rotations with weekly academic days that included this novel curriculum.Curriculum, Tool or Material : Didactic lectures, procedural workshops and simulation were closely integrated in TTD to address EPA 1. Lectures introduced approaches to cardinal presentations. An interactive workshop introduced ACLS and PALS algorithms and defibrillator use. Three simulation sessions focused on ACLS, shock, airway, trauma and the altered patient. A final simulation session allowed spaced-repetition and integration of these topics. After the completion of TTD, residents participated in a six-scenario simulation OSCE directly assessing EPA 1.Conclusion : The curriculum was evaluated using a multifaceted approach including surveys, self-assessments, faculty feedback and OSCE performance. Overall, the curriculum achieved its goal in addressing EPA 1. It was well-received by faculty and residents. Residents rated the sessions highly, and self-reported improved confidence in assessing unstable patients and adhering to ACLS algorithms. The simulation OSCE demonstrated expected competency by residents in EPA 1. One limitation identified was the lack of a pediatric simulation session which has now been incorporated into the curriculum. Moving forward, this innovative curriculum will undergo continuous cycles of evaluation and improvement with a goal of applying a similar design to other stages of CBD.